The Training of Morphological Decomposition in Word Processing and Its Effects on Literacy Skills - Bar-Kochva, Irit; Hasselhorn, Marcus (Frontiers in Psychology, 2017)
This study set out to examine the effects of a morpheme-based training on reading and writing in 5th and 6th graders (N=47), who have poor literacy skills and speak German as a second language. A computerized training, consisting of a visual computerized lexical decision task (comprising 2880 inflections and derivations, presented in 12 sessions), was designed to encourage fast morphological analysis in word processing. The children were divided between two groups: the one underwent a morpheme-based training, in which word-stems of words were presented for a limited duration, while pre- and suffixes remained on screen until response. Another group received a control training consisting of the same task, except that the duration of presentation of a non-morphological unit was restricted. In a Word Disruption Task, participants read words under three conditions: morphological separation (with symbols separating between the words' morphemes), non-morphological separation (with symbols separating between non-morphological units of words) and no-separation (with symbols presented at the beginning and end of each word). The group receiving the morpheme-based program improved more than the control group in terms of word reading fluency in the morphological condition. The former group also presented similar word reading fluency after training in the morphological condition and the in no-separation condition, thereby suggesting that the morpheme-based training contributed to the integration of morphological decomposition into the process of word recognition. At the same time, both groups similarly improved in other measures of word reading fluency. With regard to spelling, the morpheme-based training group showed a larger improvement than the control group in spelling of trained items, and a unique improvement in spelling of untrained items (untrained word-stems integrated into trained pre- and suffixes). The results further suggest some contribution of the morpheme-based training to performance in a standardized spelling task. The morpheme-based training did not, however, show any unique effect on comprehension. These results suggest that the morpheme-based training is effective in enhancing some basic literacy skill in the population examined, i.e. morphological analysis in word processing and the access to orthographic representations in spelling, with no specific effects on reading fluency and comprehension.